Hypohidrotic ectodermal dysplasia - Agarwal, Saurabh (Medknow Publications & Media Pvt Ltd, 2012)
Hypohidrotic ectodermal dysplasia (HED) is a rare genetic disorder characterized by the faulty development of the ectodermal structure, resulting in most notably anhydrosis/hypohydrosis, hypotrichosis and hypodontia. The condition is usually an X-linked recessive disorder affecting predominantly males. We are here reporting a classical case of hypohidrotic ectodermal dysplasia with a review of the literature.